Equivalent‐quality unflattened photon beam modeling, planning, and delivery. (8th July 2013) - Huang, Yunfei; Flynn, Ryan T.; Alfredo, R.; Siochi, C.; Bayouth, John E.
Abstract : The clinical application of the flattening filter‐free photon beam (FFF) has enjoyed greater use due to its advantage of reduced treatment time because of the increased dose rate. Its unique beam characteristics, along with the very high‐dose rate, require a thorough knowledge of the capability and accuracy in FFF beam modeling, planning, and delivery. This work verifies the feasibility of modeling an equivalent quality unflattened photon beam (eqUF), and the dosimetric accuracy in eqUF beam planning and delivery. An eqUF beam with a beam quality equivalent to a conventional 6 MV photon beam with the filter in place (WF) was modeled for the Pinnacle 3 TPS and the beam model quality was evaluated by gamma index test. Results showed that the eqUF beam modeling was similar to that of the WF beam, as the overall passing rate of the 2 % / 2 mm gamma index test was 99.5% in the eqUF beam model and 96% in the WF beam model. Hypofractionated IMRT plans were then generated with the same constraints using both WF and eqUF beams, and the similarity was evaluated by DVH comparison and generalized 3D gamma index test. The WF and eqUF plans showed no clinically significant differences in DVH comparison and, on average > 98 % voxels passed the 3 % / 3 mm 3D gamma index test. Dosimetric accuracy in gated phantom delivery was verified by ion chamber and film measurements. All ion chamber measurements at the isocenter were within 1% of calculated values and film measurements passed the 3 mm / 3 % gamma index test with an overall passing rate > 95 % in the high‐dose and low‐gradient region in both WF and eqUF cases. Treatment plan quality assurance (QA), using either measurement‐based or independent calculation‐based methods of ten clinically treated eqUF IMRT plans were analyzed. In both methods, the point dose differences were all within 2% difference. In the relative 2D dose distribution comparison, > 95 % points were within 3% dose difference or 3 mm DTA. PACS number: 87.55.kh